2019
DOI: 10.30534/ijeter/2019/197122019
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Labour Safety on Coal Mines

Abstract: The article provides an overview of the main classifications and concepts of human error and human factor in relation to the coal industry. The main issues have been identified, the solution of which will reduce the probability of erroneous actions of the working staff to 70-90%. According to the authors, at the present stage of the development of the coal industry in the Russian Federation, an important issue is the introduction to manning tables of specialists in the study of human factors (ergonomics).Paten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The AZRF's mineral and raw material base comprises a wide range of minerals: high-quality coal [40][41][42][43], iron, manganese, gold, nickel, copper, etc. However, due to hydrocarbon reserves [44,45], the Arctic is considered to be the most important geopolitical and geo-economic macro-region.…”
Section: Resultsmentioning
confidence: 99%
“…The AZRF's mineral and raw material base comprises a wide range of minerals: high-quality coal [40][41][42][43], iron, manganese, gold, nickel, copper, etc. However, due to hydrocarbon reserves [44,45], the Arctic is considered to be the most important geopolitical and geo-economic macro-region.…”
Section: Resultsmentioning
confidence: 99%
“…Surface and groundwater pollution as well as logging are among the biggest environmental problems associated with coal mining in Vietnam [48]. Minimizing negative impact on the environment and ensuring both occupational and product safety are prerequisites for production sustainability [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…This can also provide the worker's safety, increase the worker's productivity, and give job satisfaction and the worker's physical and mental well-being [12]. The mining company in Russia started to apply ergonomics to enhance the worker's safety as human error has been a key factor in coal industrial accidents [13]. A study on ergonomics intervention by Esmaeilzadeh and associates [14] showed that after over 6 months of ergonomics intervention, the intensity, duration, and frequency of work-related upper extremity musculoskeletal disorders (WUEMSDs) symptoms among computer workers decreased significantly.…”
Section: Ergonomicmentioning
confidence: 99%